Pendayagunaan zakat untuk beasiswa pendidikan perspektif mazhab Syafi’i dan Hanafi - Abdullah, Abdullah; Fathullah, Fathullah (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2023)
Zakat is giving a portion of the wealth that has reached the nisab, without any constraints that are not given to it. But the problem is that after it is collected and will be given to the rightful 8 asnaf (QS.: 9: 60) including certain criteria of people who are not directly mentioned by the verse above. This is evident when the wealth is given to school dropouts who want to continue with economic reasons that do not support, so everything fails in the middle of the road (Not realized). The form of the problem above is how the views of the Shafi'i and Hanafi madhhabs on the use of zakat for scholarships and where are the points of similarity and difference in the opinions of the two madhhabs. This research uses a Library Research approach (library research) After the data is collected, data analysis is continued, by checking the data (editing), marking the data (systematizing) and systematizing the data (systematizing). The type of research used in this research uses comparative studies. From the discussion above, it can be concluded that the use of zakat assets for scholarships (education costs) is permitted according to the Shafi'i madzhab and the Hanfi madzhab, as an expansion of the meaning of sabilillah or ibnu sabil, the similarity of opinion lies in the permissibility of zakat assets for education costs for those in need. The clear difference is shown by the interpretation of the meaning of sabilillah and lilfuqara' which the Shafi'i madhhab gives a broad meaning, and the use of zakat treasures for educational expenses is for those who have achievements only, but the Hanafi madhhab is more restrictive on the existence of ownership (attached to a person) about his state of lack or need of wealth.